CHARACTERISTICS OF JAPANESE HOUSEHOLDâS DEMAND - Widodo, Tri; Donna, Duddy Roesmara (Journal of Indonesian Economy and Business, 2009)
This paper estimates and analyzes the characteristics of Japanese householdâs demandÂ on goods and services, i.e. (1) Food, (2) Housing, (3) Fuel, light and water charges, (4)Furniture and household utensils, (5) Clothes and footwear, (6) Medical care, (7)Â Transportation and communication, (8) Education, (9) Reading and recreation, and (10)Other living expenditure. This paper applies Linear Expenditure System (LES) model andÂ seemingly uncorrelated regression (SUR) estimation method. Put (10) other livingÂ expenditure aside, this paper has exhibited some conclusions. First, increases in income(above supernumerary income) will be proportionally allocated more for (1) Food, (5)Â Clothes and footwear, (9) Reading and recreation, (7) Transportation and communicationÂ and (8) Education. Second, both demand and cross-price elasticities are inelastic. Third,Â demand on (4) Furniture and household utensils, (5) Clothes and footwear and (6)Â Education are income elastic.Keywords: elasticity, Linear Expenditure System (LES), Seemingly UncorrelatedRegression (SUR)